Sulfobutylether-beta-cyclodextrin-enabled antiviral remdesivir: Characterization of electrospun- and lyophilized formulations - Szente, Lajos (Carbohydr Polym, 2021)
Veklury™ by Gilead Sciences, Inc., containing antiviral drug, remdesivir (REM) has received emergency authorization in the USA and in Europe for COVID-19 therapy. Here, for the first time, we describe details of the non-covalent, host-guest type interaction between REM and the solubilizing excipient, sulfobutylether-beta-cyclodextrin (SBECD) that results in significant solubility enhancement. Complete amorphousness of the cyclodextrin-enabled REM formulation was demonstrated by X-ray diffraction, thermal analysis, Raman chemical mapping and electron microscopy/energy dispersive spectroscopy. The use of solubilizing carbohydrate resulted in a 300-fold improvement of the aqueous solubility of REM, and enhanced dissolution rate of the drug enabling the preparation of stable infusion solutions for therapy. 2D ROESY NMR spectroscopy provided information on the nature of REM–excipient interaction and indicated the presence of inclusion phenomenon and the electrostatic attraction between anionic SBECD and nitrogen-containing REM in aqueous solution.